1973
DOI: 10.1007/bf01397962
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of charged particles and radiation reaction in strong plane and spherical waves. II

Abstract: Particle motion in a superstrong wave field (Laser or Pulsar field) is considered in the presence of an additional longitudinal magnetic field. It is shown that the particle motion is distinctly different from that in a previously considered pure wave field and that the maximum obtainable energy is substantially reduced. We also reconsider the effects of radiation reaction on a particle moving in a plane linearily polarized wave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In [33] a general method of solving the LL equation in a plane wave is presented; however, as a result, the solution is given in implicit form and the solution of one integro-differential equation is required. An application of this method can be found in [10] in the particular case of a monochromatic, linearly polarized plane wave but, as we will see, the solution found is incorrect (see also [14]). Numerical approaches to the LL equation in a plane wave can be found in the literature, for studying the effects of the radiation back-reaction on the electron trajectory [19] and on the frequency spectrum of the radiation emitted by the electron [5,19,21,22].…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…In [33] a general method of solving the LL equation in a plane wave is presented; however, as a result, the solution is given in implicit form and the solution of one integro-differential equation is required. An application of this method can be found in [10] in the particular case of a monochromatic, linearly polarized plane wave but, as we will see, the solution found is incorrect (see also [14]). Numerical approaches to the LL equation in a plane wave can be found in the literature, for studying the effects of the radiation back-reaction on the electron trajectory [19] and on the frequency spectrum of the radiation emitted by the electron [5,19,21,22].…”
mentioning
confidence: 93%
“…The solution presented in [10] for the particular case of a monochromatic, linearly polarized wave does not contain the term proportional to h 2 (φ) − 1 (see Eq. (11)) which is already crucial to fulfilling the physical constraint (u(φ)u(φ)) = 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance Heintzmann & Grewing (1972) studied particle acceleration and radiation reaction in plane and spherical waves, see also Grewing et al (1975) for radiation effects in pulsar fields. Grewing et al (1973) then showed that the presence of a longitudinal magnetic field significantly reduces the maximum Lorentz factor of the accelerated particles. Surprisingly, radiation reaction is able to increase the asymptotic Lorentz factor of the charged particle when interacting for instance with an intense laser pulse as shown by Fradkin (1979).…”
Section: Introductionmentioning
confidence: 99%